Formulation and Evaluation of Taste Masked Oral Disintegrating Tablet of Lornoxicam - S. K. SHETH; S. J. PATEL; J. B. SHUKLA (International Journal of Pharma and Bio Sciences, 2010)
Lornoxicam is a non steroidal anti-inflammatory drug with analgesic properties. The purpose of this study was to develop a taste masked oral disintegrating tablet of poorly soluble Lornoxicam by direct compression technique with β-cyclodextrin (BCD) complexes using various super disintegrants like sodium starch glycolate, crospovidone and croscarmellose sodium. Prepared tablets were evaluated for different properties like drug content, hardness, friability, disintegration time and in vitro dissolution study. The different formulations showed disintegration time between 22 to 58 s. Drug release showed time between the ranges of 8 to 20 min. Among all the formulations, L6 showed 99.85% drug release within 8 min. Thus, L6 was considered best among the other formulations. The stability study was conducted as per the ICH guidelines and the formulations were found to be stable, with insignificant change in hardness, drug content and disintegration time. The tablets showed enhanced dissolution hence better patient compliance.